Reliability assessment and correlation analysis of 3 protocols to measure trunk muscle strength and endurance - Juan-Recio, C.; López-Plaza, D.; Barbado Murillo, D.; Garcia-Vaquero, M. P.; Vera-Garcia, F. J. (Journal of Sports Sciences, 2018)
Different methods have been developed to quantify trunk muscle strength and endurance. However, some important protocol characteristics are still unclear, hindering the selection of the most suitable tests in each specific situation. The aim of this study was to examine the reliability and the relationship between 3 representative tests of the most common type of protocols used to assess trunk muscle strength and endurance. Twenty-seven healthy men performed each test twice spaced 1 month apart.Trunk strength and endurance were evaluated with an isokinetic dynamometer and 2 field tests including Biering-Sørensen test and Flexion-rotation trunk test.